2020
DOI: 10.4136/ambi-agua.2541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inoculum/substrate ratio on the biochemical methane potential (BMP) of grape marc

Abstract: The grape industrialization process produces large volumes of solid organic waste, with the grape bagasse being the main waste generated in the winemaking process. Anaerobic digestion can be used to treat and dispose of agro-industrial biomass waste. The objective of this study was to evaluate the effect of the inoculum/substrate ratio on the Biochemical Methane Potential (BMP) of grape marc. The experiment was performed in laboratory scale through a system of reactor bottles in batches, removing a set of trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
0
1
1
Order By: Relevance
“…In the current study, the results showed that methane yields increased at a higher ISR, and are in agreement with previous studies in which different substrates have been used (Silva et al, 2020;Córdoba et al, 2018;Raposo et al, 2009;Wei et al, 2014). An optimal ISR in the biodigester is considered to contain the balanced amount of anaerobic microorganisms for the digestion of primary and intermediate products (Eskicioglu and Ghorbani, 2011).…”
Section: Effect Of Isr On Biomethane Potential and Biodigester Stabilitysupporting
confidence: 93%
“…In the current study, the results showed that methane yields increased at a higher ISR, and are in agreement with previous studies in which different substrates have been used (Silva et al, 2020;Córdoba et al, 2018;Raposo et al, 2009;Wei et al, 2014). An optimal ISR in the biodigester is considered to contain the balanced amount of anaerobic microorganisms for the digestion of primary and intermediate products (Eskicioglu and Ghorbani, 2011).…”
Section: Effect Of Isr On Biomethane Potential and Biodigester Stabilitysupporting
confidence: 93%
“…The authors explained that the stable woody substrates of P&P WAS, including cellulose and lignin, may be responsible for the low biodegradability when compared with sewage sludge. Nevertheless, the results are superior to those reported for other organic materials, such as: peanut shells (84-157 mL CH4/gVS), coffee husks (116-155 mL CH4/gVS) [40], fresh 4190 grass and silage (125-186 mL CH4/gVS) [48] and grape marc (19-64 mL CH4/gVS) [49]. Table 12 shows the comparison with other studies, where it is demonstrated that pulp mill WAS is a promising substrate for methane production.…”
Section: Methane Productioncontrasting
confidence: 67%
“…2023 (2020) para uma alta produtividade de biogás. Silva et al (2020), estudando o efeito da relação inóculo/substrato (I/S) no potencial bioquímico de metano do bagaço de uva observaram que a relação I/S 3 proporcionou os melhores resultados para carregamento de sistemas anaeróbios, indicando que o bagaço de uva apresenta potencial para tratamento biológico por digestão anaeróbia. Substrato, quimicamente, similar a alguns tratamentos deste trabalho.…”
Section: Tratamentos ------------Entrada------------------------saída...unclassified